Anticipate the freedom - Natalia Laino Topham (Oñati Socio-Legal Series)
For the purpose of understanding the processes of expert assessment (carried out by psi operators and judicial operators) that women deprived of liberty get through in Uruguay to access the benefit of anticipated freedom and how they are associated with the construction of their dangerousness, four analytical axes are raised which configure the expert practices as practices of production of the truth. This research was conducted with a qualitative methodology, with interviews, documentary analysis and participant observation. The analysis reveals a strong invisibility of women in the penal system, the presence of the empiricist repertoire (objectivity, impartiality, neutrality), the presence of confession and the value of repentance with a privileged place in the evaluation practices, the psi contribution in the construction of a biography installing the fiction of the subject as a determination, and the psi participation in a general framework of control, surveillance and management of the populations.